THE LATENT INTERCONNECTION OF THE FACTORS OF ATHEROSCLEROSIS PROGRESSION WITH A THICKNESS OF INTIMA-MEDIA BY USE OF MULTIDIMENSIONAL STATISTICAL METHODS ANALYSIS - A. P. Shavrin; Y. B. Hovaeva; B. V. Golovskoy (Klinicist, 2014)
The aim – the study of latent relationships between indicators of the thickness of intima-media (CMM) and infectious, immune, inflammatory and metabolic factors in patients with varying degrees of severity of vascular changes in these multivariate methods of statistical analysis. Materials and methods. Study included 220 patients (mean age – 43,9 ± 0,5 years) who were divided into 3 groups. Group 1 consisted of thepatients with no risk factors of cardiovascular disease (CVD), the 2nd – the presence of the above factors, in third – with atherosclerotic plaques in the carotid artery. Every patient had conducted a comprehensive survey, which included an ultrasound of vessels on the apparatus Aloka 5000 with the measurement of the thickness of KIM, the study of lipid panel, the definition of C-reactive protein and cytokines – tumor necrosis factor-α, interferon-γ, interleukin-1, -8, -4, antibodies to cytomegalovirus immunoglobulin (CMV), herpes simplex virus type 1, C. pneumoniae, H. pylori and β-hemolytic streptococcus group A. The immune system status was assessed by indicators of innate and acquired immunity. Results. According to cluster analysis, all groups of patients revealed the presence of close relationships with linear thickness KIM, infectious, immune and metabolic markers, and in patients with atherosclerotic plaques in blood vessels links with indicators of inflammation are additionally found. Using factor analysis latent variables exist revealed, consisting of indices and thickness of the CMM, in group 1 – blood lipids, in the 2nd – infectious factors (CMV, C. pneumoniae) and immune parameters. In the 3rd group vascular wall was linked with infectious diseases, immune and inflammatory indices and blood lipids, and systolic and diastolic blood pressure. Conclusion. The closest relationship with vascular wall of the studied parameters was observed in patients with risk factors of cardiovascular disease, and in the presence of atherosclerosis. To implement the pathological process in the vessel are important factors of acquired immunity depression, chronic intracellular infections, and possibly associated with it inflammatory process.